HAKIKAT KURIKULUM PENDIDIKAN ISLAM - Nidawati Nidawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The curriculum is a tool to achieve educational goals, where the components of the curriculum must be interrelated and provide direction for goals that contain values that are believed to be true. The Islamic education curriculum has different characteristics, where the principles and materials are sourced from the Qur'an and al-hadith. The Islamic education curriculum must be designed and formulated in a clear and well-planned manner that outlines a series of knowledge that must be taught by educators to students and also for all educational activities that influence students in order to achieve the goals of Islamic education.